2020
DOI: 10.21106/ijtmrph.133
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar Puncture in Saudi Arabia: Knowledge, Awareness, Acceptance and its Refusal Among Health Professionals

Abstract: BACKGROUND AND OBJECTIVES: Lumbar puncture (LP) is a standard technique to acquire cerebrospinal fluid (CSF) for either diagnostic or therapeutic management of neurological disorders. This study assesses the awareness and level of acceptance of LP among medical laboratory students. The study also investigates the level of understanding of the purpose of performing LP and determines the acceptance rate among the study population. METHODS: A cross-sectional study was conducted in Taif, Saudi Arabia, using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Although Saudi Arabia claims to be the first country in the Arab world to have more than 10,000 stem cell donors, it is currently underperforming in this domain as compared to European and other developed countries. According to available statistics, the rates of registered stem cell donors are just around one per cent in Saudi Arabia [ 3 ]. The underlying factors responsible for this scenario could be lack of awareness about basic facts such as sources of adult stem cells, procedures of adult stem cell retrieval, donation risks and outcomes and information about authorized local and international donor agencies etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although Saudi Arabia claims to be the first country in the Arab world to have more than 10,000 stem cell donors, it is currently underperforming in this domain as compared to European and other developed countries. According to available statistics, the rates of registered stem cell donors are just around one per cent in Saudi Arabia [ 3 ]. The underlying factors responsible for this scenario could be lack of awareness about basic facts such as sources of adult stem cells, procedures of adult stem cell retrieval, donation risks and outcomes and information about authorized local and international donor agencies etc.…”
Section: Introductionmentioning
confidence: 99%
“…One study from the Mecca region of Saudi Arabia assessed the acceptance and refusal rates for stem-cell registration in a sample of around 500 participants. Findings showed that only 1.8% of respondents were registered with stem cell donation organization despite 96% were willing to donate stem cells in case if it is needed for the treatment of a family member [ 3 ]. This shows that their willingness to donate stem cells is largely conditional.…”
Section: Introductionmentioning
confidence: 99%